Pilot Study of a Statewide Initiative to Enhance Depression Care Among Older Home Care Patients. (April 2013) - Delaney, Colleen; Fortinsky, Richard; Mills, Dana; Doonan, Lorraine; Grimes, Rita; Rosenberg, Suzanne; Pearson, Terra-Lee; Bruce, Martha L.
Late-life depression is prevalent in home care. This pilot study, part of a statewide initiative to enhance depression care, evaluated the influence of a 2-hour depression screening and intervention workshop on home care professionals' knowledge, self-efficacy, and attitudes related to depression in older home care patients. A pretest, posttest design was used to evaluate the effects of the workshop with 280 home care professionals from 7 home care agencies. Following the depression workshop, participants' knowledge levels in evidence-based screening and care for depressed older adults was significantly increased, t (280) = 16.49, p<.001. A significant increase in confidence and attitude ratings were found (p<.001). Findings from this pilot study support broader dissemination throughout Connecticut home care agencies.